The Return on Alternative Sources of Finance - Brealey, R. A.; Hodges, S. D.; Capron, D. (The Review of Economics and Statistics, 1976)
N 1970 Baumol, Heim, Malkiel, and Quandt (hereinafter BHMQ) published a provocative article. Their hypothesis was that for U.S. firms the rate of return from invested funds would be greatest when the financing involved the most serious exercise of market discipline. On these grounds they conjectured that borrowing would tend to produce significant increases in earnings but not as great as those associated with new stock issues, and that the rate of return to plowback would be the lowest of the three. BHMQ's empirical tests led them to the following conclusions: